(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
In this new era of the online world, marketing tactics have transformed to grab the attention of the customers and generate the concept of online marketing. The aim of this study is to determine the impact of online marketing tools on the online shopping behavior of the consumers in the current advanced technological environment of India. Five online marketing tools were considered: E-mail Marketing, Search Engine Marketing, Social Media Marketing, Display Advertising, and Mobile Advertising. The sample size is 542 and data were collected from New Delhi, Gorakhpur and Mumbai. For determining the impact, multiple linear regression is applied. S.P.S.S is used for analyzing the data. All five online marketing tools have a significant impact on the online shopping behavior of consumers. E-mail marketing has a substantial impact on consumer’s behavior in online shopping. The marketer has first to choose the right online marketing tool to use and then evaluate that tool in terms of, how much it contributes to the business.